Życie i działalność Bohdana Kistiakowskiego w latach 1914–1920 - Jędrysiak, Marcin (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2019)
Bogdan Kistiakovski is known as the most renowned Ukrainian legal philosopher and social scientists. His works served as an inspiration for authors such as Georg Jellinek, Hans Kelsen, Max Weber or Robert M. Park. Unforunately, in Poland his works are almost completely unknown. Existing biographies of Kistiakovsky tend to leave out the last period of his life years 1914–1920. In fact this is the most fascinating time of his activity. During World War I he published works in which he formulated the idea of the pluralistic theory of the law, edited legal journals for the elite of the Russian jurisprudence of that time. He was also actively working in the structures of the Ukrainian states: Ukrainian People’s Republic and the Ukrainian State. He became a judge for the first time in his life and took part in the works of the Ukrainian Academy of Sciences. The goal of the paper was to indicate the role Kistiakovsky played in the years 1914–1920 in Ukraine, as well as show his scientific life, with a special focus on his master’s degree dissertation. In the article the thesis that Kistiakovsky had a negativeapproach towards the Pavlo Skoropadsky’s Ukrainian state and had bad relations with his brother – Ihor, is also verified. It is also proven that Kistiakovsky was indeed very consequent in his views on the national and political questions, despite the political circumstances changing. In the paper Kistiakovsky’s scientific activity is shown. It has also been verified what was the topic of his last, unpublished papers. In the further parts, his activity as an expert in the commission for creating a Citizenship Law in Ukraine, his works in the committees for the organization of the Universities in Ukraine, as well as in the commission for the purpose of creation of the Electoral Law are described. Kistiakovsky’s work in the Ukrainian Academy of Science is also shown. The last months of his life, i.e. his activity in Katerinodar in the structures of the Kuban’ People’s Republic is also mentioned. In the summary the conclusions are formulated and the suggested further fields of research proposed.
Keywords: Kistiakovsky, Bohdan; biografia; I wojna światowa; Ukraina; Ukraińska Republika Ludowa